Factors affecting the salary of agricultural economics professionals - Abdula, Arbaiya L. (Arbaiya Ladiero) 1975- (ProQuest Dissertations & Theses Global, 2008)
Recent studies on the status of agricultural economic professionals suggest that gender and race is not a factor why there are differences in salary among them. The purpose of this research was to survey the academic agricultural economics professionals who work in 1862, 1890 and 1994 Land Grant Institutions to identify factors that affect their salary and verify if previous study holds. This research was also conducted to identify whether differences exist between men and women in the factors important in choosing their current job, the potential problems they face in their work and their salaries. Finally, this study hopes to develop a baseline dataset for future evaluation of agricultural economist. Results suggest that the salary of agricultural economist is not determined by his/her gender and race but rather by factors like tenure, highest rank within university, type of land grant institution where employed, number of refereed articles published, grant funds and his/her perceptions on the importance of family time. This paper also suggests that significant differences do exist between men and women in some of the factors that are important in their job choice including: salary, health benefits, pension, availability of supportive colleagues, tenure opportunity, non-discrimination by their employers and opportunities for partners. Significant differences also exist in problems they face in their work including: lack of supportive colleagues, time available for family, negative work environment, lack of mentors, available time for children, employer perceptions, professional isolation, partner mobility, social isolation, and discrimination.